The Christian faith of Charles Dickens: virtue over doctrine - Eyeons, Melanie (2025)
This thesis explores the religious worldview of Charles Dickens. It is intended as a contribution to the debate around whether Dickens had a truly Christian faith, or alternatively a confused mixture of beliefs, or even no faith at all. The thesis argues that Dickens had a distinctively Christian faith that stressed faith in action and displaying virtues within a Christian framework, rather than focusing on determining correct theology and doctrine. Dickens’ reactions to both Evangelicalism and Catholicism are explored to determine the nature of his objections to both and what these objections reveal about Dickens’ own beliefs. It is argued that Dickens’ criticisms of both faith traditions reveal his concern that Christianity should primarily consist in actively following the example of Jesus by displaying care for others in a spirit of Christian charity, goodness, and compassion. Dickens’ attitudes towards women, death, and the afterlife are also explored, and the thesis reveals that Dickens’ religious interests went beyond the purely social concern for which he is known. The thesis makes another contribution by breaking with previous research and emphasising Dickens’ magazine work and personal correspondence. These elements of Dickens’ writing and editing are generally considered secondary to his novels and frequently overlooked. However, this research shows that Dickens’ magazines and letters are rich sources of information that provide a more holistic view of Dickens’ religious views, since he more often directly addresses religious matters within them than he does in his novels. It is hoped that this thesis will show the importance of looking beyond just the published novels of Dickens, or indeed other authors, and encourage further studies that use other sources.